Effect of COVID-19 on Cardiovascular Disease Mortality in a Medium-Sized City (Epidemiology, Biostatistics, and Public Health, 2024)
Introduction: Patients hospitalized for COVID-19 have a high prevalence of cardiovascular risk factors, such as hypertension and diabetes mellitus, in addition to chronic cardiovascular conditions, such as ischemic heart disease and heart failure. Other fatal events have also occurred, and are somehow indirectly associated with the pandemic, such as deaths from neglected or inadequately treated diseases due to an overburdened health system or fear of leaving home at the height of the COVID-19 pandemic. The present study aims to evaluate the impact of COVID-19 on CVD statistics in a medium-sized city.Methods: A retrospective observational study with 546 patients who died due to cardiovascular diseases, between January 1, 2019 and December 31, 2020. Regarding the year of death, continuous variables were compared using the unpaired t-test and categorical variables using Pearson’s chi-square or Fisher’s exact test. Considering a significance level of 0.05 in the two-tailed test.Results: A total of 545 deaths due to cardiovascular diseases were evaluated, 272 in 2019 and 274 cases in 2020. There was no difference in age and sex ratios between the years evaluated. There was a higher frequency of deaths at home in 2020 compared to 2019; a reduction in the frequency of deaths occurring in hospitals.Conclusion: The results indicate an increase in the number of deaths at home due to CVD reported by SIM in 2020 compared to the same period in the previous year, in a medium-sized Brazilian city.
Keywords: Covid-19; myocardial infarction; heart failure; death; Cardiovascular Diseases